Balloon test occlusion of internal carotid artery: Angiographic findings predictive of results - Kikuchi, Kazufumi (Baishideng Publishing Group Inc, 2014)
AIM: To reveal angiographic findings to predict the result of balloon test occlusion (BTO). METHODS: The cerebral angiograms of 42 consecutive patients who underwent cerebral angiography including both the Matas and Allcock maneuvers and BTO were retrospectively analyzed. Visualization of the anterior cerebral artery (ACA) and the middle cerebral artery (MCA) by the cross flow on the tested side during the Matas or Allcock maneuver was graded on a 5-point scale. Circle of Willis (COW) anatomy with respect to the presence/absence of a collateral path to reach the tested internal carotid artery (ICA) was classified into four categories. A univariate logistic analysis was used to analyze the associations between each angiographic finding and the BTO result. Sensitivity, specificity, accuracy, positive predictive value, and negative predictive value for each finding were calculated. RESULTS: Five patients (12%) were BTO-positive and the remaining 37 patients (88%) were BTO-negative. Visualizations of the ACA and MCA as well as the COW anatomy were significantly associated with the BTO result (P = 0.0051 for ACA, P = 0.0002 for MCA, and P < 0.0001 for COW anatomy). In particular, good MCA visualization and the presence of an anterior connection (collateral path to the tested ICA from the contralateral ICA via the anterior communicating artery) in the COW were highly predictive for negative BTO (negative predictive value = 100% for both). CONCLUSION: A BTO result may be predicted by angiographic findings including ACA/MCA visualization and COW anatomy.